Negotiating and learning grammar in synchronous on-line chats among Malaysian tertiary ESL students - Samani, Ebrahim (2014)
Taking into consideration the importance of using negotiated interaction over grammatical structures through computer-mediated communication (CMC), conflicting results of attitude toward CMC, and the nature of CMC environments, the current study attempted to examine immediate and long-time effect of negotiated interaction on students’ achievement in grammar in Malaysian context. The study also sought to evaluate opinions of participants in this study regarding CMC. Furthermore, it focused on gaining more in-depth and detailed picture of learners’ beliefs and experiences of their interaction over grammatical structures in written synchronous computer-mediated communication (SCMC). Finally, the aim of this study was also to analyze the discourse patterns of text-based CMC in terms of negotiation functions. These aims were addressed using an experimental research design. Fifteen students from Universiti Putra Malaysia (UPM) participated in the study. All of these students were undertaking Bachelors of Education undergraduate program, with specialization in teaching English as a second language (TESL). The students were involved in written interaction via text-chat over sentence combining activities with an aim to practice preselected grammatical structures. Pretests, posttests, and delayed posttests were administered to measure students’ achievement in grammar. Findings of the study indicated that there were statistically significant differences on the outcomes of pre, post, and delayed posttests for the students who involved in negotiated interactions over preselected grammatical structures. The second major finding was that participants’ attitude toward computer-mediated communication (CMC) did not show any significant changes. Furthermore, results from the interview conducted indicated anonymity, feedback, durability, involvement in learning, individualized instruction, time, comfortable environment, and contextualized instruction as the beneficial effects of involving in negotiated interaction over preselected grammatical structures through the medium of written SCMC. In terms of negotiation functions, the most frequent function was confirmation check and the least frequent one was reply confirmation. The beneficial effects of negotiated interactions through written SCMC were confirmed according to the findings of this study. This clearly shows that negotiated interactions via CMC can indeed be an effective pedagogical tool for teachers to improve students’ grammatical knowledge.